2016
DOI: 10.1002/jcsm.12054
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside alleviates cachexia symptoms in mouse models of cancer cachexia via activating mTOR signalling

Abstract: BackgroundCachexia has a devastating impact on survival and quality of life for many cancer patients and contributes to nearly one‐third of all cancer deaths; also, it is associated with poor responses to chemotherapy and survival. A better understanding of the underlying mechanisms of cancer‐associated cachexia (CAC), coupled with effective therapeutic approaches, will improve management of progressive functional impairment in cancer patients. Salidroside, a phenylpropanoid glycoside in Rhodiola rosea L, has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 33 publications
2
43
1
1
Order By: Relevance
“…In addition, salidroside was shown to promote angiogenic differentiation of human bone marrow-derived endothelial progenitor cells [105] and to protect against oxidative endothelial injury by activation of the mTOR pathway [105107]. Salidroside also inhibited CT-26 and Lewis lung carcinoma tumor-induced cachexia and the loss of tumor-free body weight, adipose and gastrocnemius muscles, as well as extended the survival of the treated mice by increasing the expression of phosphorylated mTOR both in C2C12 myotubes and in gastrocnemius muscle of the mice [108]. These results suggested that salidroside has a text-dependent effect on the mTOR pathway.…”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
“…In addition, salidroside was shown to promote angiogenic differentiation of human bone marrow-derived endothelial progenitor cells [105] and to protect against oxidative endothelial injury by activation of the mTOR pathway [105107]. Salidroside also inhibited CT-26 and Lewis lung carcinoma tumor-induced cachexia and the loss of tumor-free body weight, adipose and gastrocnemius muscles, as well as extended the survival of the treated mice by increasing the expression of phosphorylated mTOR both in C2C12 myotubes and in gastrocnemius muscle of the mice [108]. These results suggested that salidroside has a text-dependent effect on the mTOR pathway.…”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
“…have also indicated that dihydrotestosterone could rescue an age‐dependent reduction in protein synthesis of skeletal muscle fibres in sarcopenic mice . A natural product, salidroside, sourced from Rhodiola rosea L., has been found to exhibit potential therapy against cancer‐associated cachexia‐induced limb muscle loss in tumour‐borne BALB/c mice, including gastrocnemius (Gascn) muscles . Moreover, anamorelin, a ghrelin‐analog, could show an increase in muscle mass in cancer anorexia‐cachexia syndrome .…”
Section: Introductionmentioning
confidence: 99%
“…20 A natural product, salidroside, sourced from Rhodiola rosea L., has been found to exhibit potential therapy against cancer-associated cachexia-induced limb muscle loss in tumour-borne BALB/c mice, including gastrocnemius (Gascn) muscles. 21 Moreover, anamorelin, a ghrelin-analog, could show an increase in muscle mass in cancer anorexia-cachexia syndrome. 22 It is critical to discover the potential interventions against muscle wasting from sarcopenia, cachexia, and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The future pipeline of therapeutic interventions will be enhanced by the dissemination of basic reports into preclinical models [34][35][36][37] and early human trials 38 as a way of evaluating novel interventions. [39][40][41][42] One of the major advantages of having JCSM as a leader in this field is that such opportunities can more easily be found, rather than being spread over dozens of different journals.…”
Section: By Methodsologymentioning
confidence: 99%
“…27,28 There was growing evidence for the development of clinical trials and for improvements in clinical trial methodology by the development and validation of clinical screening tools 29 and scoring systems, 30 biomarkers, 31,32 and evaluative methodologies, including the establishment of normal ranges. 33 These may help make trial design and novel treatment evaluation more precise in the future.The future pipeline of therapeutic interventions will be enhanced by the dissemination of basic reports into preclinical models [34][35][36][37] and early human trials 38 as a way of evaluating novel interventions. [39][40][41][42] One of the major advantages of having JCSM as a leader in this field is that such opportunities can more easily be found, rather than being spread over dozens of different journals.There was a noticeable increase compared to earlier years of the journal in orthopaedic and musculoskeletal clinical reports.…”
mentioning
confidence: 99%